Experimental Impacts of the “Quality Preschool for Ghana” Interventions on Teacher Professional Well-being, Classroom Quality, and Children’s School Readiness - Wolf, Sharon; Aber, J. Lawrence; Behrman, Jere R.; Tsinigo, Edward (Journal of Research on Educational Effectiveness, 2019)
We assessed the impacts of a teacher professional development program for public and private kindergartens in the Greater Accra Region of Ghana. We examined impacts on teacher professional well-being, classroom quality, and children’s readiness during one school year. This cluster-randomized trial included 240 schools (teachers N ¼ 444; children N ¼ 3,345, Mage ¼ 5.2) randomly assigned to one of three conditions: teacher training (TT), teacher training plus parental-awareness meetings (TTPA), and controls. The programs incorporated workshops and in-classroom coaching for teachers and video-based discussion groups for parents. Moderate impacts were found on some dimensions of professional well-being (reduced burnout in the TT and TTPA conditions, reduced turnover in the TT condition), classroom quality (increased emotional support/behavior management in the TT and TTPA conditions, support for student expression in the TT condition), and small impacts on multiple domains of children’s school readiness (in the TT condition). The parental-awareness meetings had counteracting effects on child school readiness outcomes. Implications for policy and practice are discussed for Ghana and for early childhood education in low- and middle-income countries.
Keywords: Ghana; ___working_potential_duplicate; classroom quality; early childhood education; kindergarten; school readiness; teacher training and coaching

Ministry of Education Ghana - Education Strategic Plan 2018-2030 - Ministry of Education, Ghana (Ministry of Education, Ghana, 2019)
Building on Ghana's achievements in expanding education, the Education Strategic Plan sets out the vision and policies for realizing the ambition of transforming Ghana into a ‘learning nation'. It puts Ghana on the road towards meeting the Sustainable Development Goals and represents a deliberate reorientation towards this aim, as it replaces the previous ESP for 2010-2020. This plan not only sets the long-term vision but also how this will be operationalized in the medium term through the accompanying Education Sector Medium Term Development Plan 2018-2021.

OU partners with Ministry of Education in Ghana to launch OpenSTEM Africa - Grimmette, Hannah (OU News, 2019)
The Open University and the Ministry of Education (Ghana) have launched a programme to promote the effective teaching of practical science in Senior High Schools. Open STEM Africa: Ghana, is aimed at improving practical teaching and learning of science and in particular providing support for under-qualified or inexperienced science teachers, in line with the government of Ghana’s education policy.

Gauging the E-Readiness for the Integration of Information and Communication Technology Into Pre-Tertiary Education in Ghana: An Assessment of Teachers' Technological Pedagogical Content Knowledge (TPACK) - Gyaase, Patrick Ohemeng; Gyamfi, Samuel Adu; Kuranchie, Alfred (International Journal of Information and Communication Technology Education (IJICTE), 2019)
Countries are investing in information and communication technology (ICT) infrastructure and educating their citizens for effective ICT utilization. The attainment of the anticipated benefits hinges on effective integration of ICT in various levels of education. Effective integration of ICT requires...

Education Strategic Plan 2018–2030 - Ministry of Education, Ghana (Ministry of Education, Ghana, 2019)
Building on Ghana's achievements in expanding education, this plan puts Ghana on the road towards meeting the Sustainable Development Goals and represents a deliberate reorientation towards this aim, as it replaces the previous ESP 2010-2020.

The Opportunities and Challenges for Developing ICT-Based Science Learning and Teaching in Ghana - Cullen, Jane; Mallet, Joshua (2019)
Africa’s transition to an innovation-led, knowledge-based economy could drive the continent’s economic growth and lift millions out of poverty and there is opportunity to increase the number of skilled professionals across the chemistry, biology and physics disciplines. However not enough students enrol in science subjects in Higher Education in Ghana, with proportions admitted to public universities well short of the Government’s 60% target. Significant barriers for all young people include the lack of practical scientific equipment in schools, and barriers to young women include prevailing socio-cultural attitudes, a lack of female role models and unsupportive educational environments.

Ghana Beyond Aid Charter and Strategy Document (Draft) - Ministry of Education, Ghana (Ministry of Education, Ghana, 2019)

Factors That Influence Teachers' Pedagogical Use of ICT in Secondary Schools: A Case of Ghana - Buabeng-Andoh, Charles (Contemporary Educational Technology, 2019)
Technology is perceived as a vital driving force for contemporary education. The Government of Ghana acknowledges the relevance of Information and Communication Technology (ICT) in education, and it is financing ICT in secondary schools. However, most instructors are unwilling to integrate ICT into their teaching. Therefore, the purpose of this study was to investigate the factors that influence secondary school teachers' ICT usage in schools. The participants were 376 teachers randomly selected from 24 public and private schools. The data collected from the participants were analyzed by using descriptive statistics and analysis of variance. The results showed that teachers' use of ICT was still confined to basic and traditional activities such as search for information, class presentation etc. Internal and external factors were found to influence teachers' ICT usage. Also, female teachers reported that they use ICT more than male teachers. In general, this study has contributed to the literature regarding teachers' pedagogical use of ICT in secondary schools and also their gender differences in the use of ICT.
Keywords: Access to Computers; Competence; Computer Uses in Education; Foreign Countries; Gender Differences; Influence of Technology; Information Technology; Instructional Leadership; Pedagogical Content Knowledge; Private Schools; Public Schools; Rural Schools; Secondary School Teachers; Secondary Schools; Self Efficacy; Teacher Attitudes; Technological Literacy; Technology Integration; Training; Urban Schools; ⛔ No DOI found

Investigating The Benefits Of Incorporating Technology In Instructional Curriculum: Pre-Service Teachers' Perspectives From Ghana - Wiafe, Bernard; Akaadom, Bernard (International Journal of Advanced Research, 2019)
The use of technology has gained worldwide recognition in all professions. Teachers have resorted to several technology tools to enhance the work they do in the classroom and to facilitate the understanding of what they teach their students to enhance easy recall and for students to remember what they learn in class. The use of technology tools in the classroom in Ghana has not received much attention from teachers because of challenges with respect to technological infrastructural development. However, with the inclusion of technology in the teacher colleges of education curriculum, new teachers are being trained to incorporate technology into classroom instruction to change the face of teaching and make learners more eager to learn by bringing the understanding of concepts much more clearly to students. The study adopted a mixed method approach to bring to light, the perspectives of teacher trainees and tutors in colleges on the benefits both the teacher and the learner stand to gain in using technologies to deliver instruction in the classroom. It came to light that although there are challenges pre-service teachers tend to face in terms of access to such technologies, they still do their best to include technologies in their lessons whenever possible. This is because of the fact that learners tend to do well on instruction received on lessons delivered using technology as compared to lessons delivered without using technology based on their experience in using both approaches in the classroom. Keywords: Technology, instruction, benefits, curriculum.
Keywords: ⛔ No DOI found

Reform Secretariat at the Ministry of Education - Ministry of Education, Ghana, Reform Secretariat (2019)
A Reform Secretariat has been formed at the Ministry of Education to ensure that all the agencies and bodies directly...

A support programme for caregivers of children with disabilities in Ghana: Understanding the impact on the wellbeing of caregivers - Zuurmond, Maria; Nyante, Gifty; Baltussen, Marjolein; Seeley, Janet; Abanga, Jedidia; Shakespeare, Tom; Collumbien, Martine; Bernays, Sarah (Child: Care, Health and Development, 2019)

Number of pay TV households in Ghana 2014-2023 - Watson, Amy (Statista, 2019)
The timeline presents the number of pay TV households in Ghana from 2014 to 2018, and a forecast thereof until 2023.

Ghana Investment Fund for Electronic Communications (2019)

The Impacts of Teacher Training and Parental Awareness on Kindergarten Quality in Ghana - Wolf, Sharon; Aber, John Lawrence; Behrman, Jere (Innovations for Poverty Action, 2019)

In Ghana, Free High School Brings Opportunity and Grumbling - Nir, S.M. (2019)

Inequalities in Human Development in the 21st Century, Ghana - UNDP (2019)

Understanding the Allocation of Public Personnel Across Government Health Facilities in Ghana - Diop, Binta Zahra; Awoonor-Williams, Koku; Ofosu, Anthony; Williams, Martin J (2019)
In order to deliver public services, governments must allocate scarce human and ﬁnancial resources across their territories, yet there is little systematic evidence on the productivity of these inputs or allocative eﬃciency with which governments allocate them. We study this by leveraging a unique panel dataset of service delivery, health outcomes, and human and ﬁnancial inputs in the universe of over 5,000 public health facilities in Ghana. Our research design allows us to estimate the marginal returns to health personnel and inputs, while controlling for unobserved heterogeneity across facilities. We document the roles and current distribution of the diﬀerent types of health workers and facilities within the health system, and investigate the relationship between patient volume and the number of health workers in a facility. We discuss implications for optimal staﬃng allocations and further research.
Keywords: ⛔ No DOI found

Ghana Mulitple Indicator Cluster Survey 2017/2018 (The Government of Ghana, 2019)

Assessment of the effectiveness of ICT on Teacher Trainees in Colleges of education. A Case of St. Monica's College of Education - Osei Frimpong, Kojo; Asare, Samuel; Caroline, Owusu-Mintah (Asian Journal of Computer Science and Information Technology, 2019)
The use of ICT in teacher training colleges has relatively improve teaching and learning. The effective use of various ICT tools such the computer, smart phones and PDAs has brought innovative ideas in teacher trainees. This study aimed at finding out the factors influencing the use of ICT tools in enhancing teaching and learning process in the various teacher training institutions in Ghana. A survey was used in order to investigate the study. It was revealed from the findings of the study that students and tutors in the various colleges of education have now accepted the use of ICT in teaching and learning process. However some students still see ICT as difficult due to various factors such as inadequate computers in the various colleges for practical tution and poor access to the internet for learning.
Keywords: ⛔ No DOI found

Transforming Teacher Education and Learning in Ghana: The Impact of a Continuous Professional Development on Physics Teaching at the Colleges of Education - Coffie, Isaac Sonful (International journal of Research and Scientific Innovation, 2019)
The colleges of education in Ghana have been involved in a continuous professional development for over four years with support of Transforming Teacher Education and Learning (T-TEL). The main purpose of this research was to assess the perceived impact of the continuous professional programme on physics teaching at the colleges of education. Descriptive cross sectional survey was used for the study. An online survey was conducted which was completed by 85 physics tutors. The survey data were analysed using means and standard deviations and ANOVA. It was found that the professional development is perceived by the physics tutors to have great impact on their teaching practice. It was also found out that there was no statistical significant difference in the perceived impact of the professional development based on tutors’ experience. It was concluded that if the student teachers who are being trained by these tutors will learn these ideas from their tutors and practice them, teaching at the basic schools will be more interactive, students-centered and gender responsive.
Keywords: ⛔ No DOI found

Integrating social media platforms into higher education pedagogy in Ghana - Appiah-Boateng, Patricia (University of Ghana, 2019)

Ghana Accountability for Learning Outcomes Project - World Bank (2019)

Communications for Development - Fink, Günther; Karlan, Dean; Udry, Christopher; Osei, Robert (Harvard Dataverse, 2019)
In 2012, Ghana Health Services (GHS), with funding from the United Nations Children’s Fund (UNICEF), launched a Communication for Development (C4D)...
Keywords: Health and Life Sciences; Medicine; Social Sciences

Learner access to resources for eLearning and preference for eLearning delivery mode in distance education programs in Ghana - Arthur-Nyarko, Emmanuel; Kariuki, Moses Githua (International Journal of Educational Technology, 2019)
Keywords: ⛔ No DOI found

Wikipedia:Text of Creative Commons Attribution-ShareAlike 3.0 Unported License - Wikipedia (Wikipedia, 2019)

Gender equity and fee-free basic education in Tanzania - Al-Samarrai, Samer; Tamagnan, Marie Evane (Education Global Practice, Africa Region, World Ban, 2019)
Samer Al-Samarrai, Marie Evane Tamagnan1 Introduced in 2016, the Fee-Free Basic Education Program (FBEP) is the government’s flagship policy to expand equitable access to basic education. Evidence shows that policies of this kind increase educational access and lead to significant economic and social benefits. In Ghana, children that received fee-free education were much more likely to complete secondary school and had much higher earnings than children that were not part of the program. In Tanzania, similar benefits to FBEP are possible since the labor market returns to secondary schooling are high.

Gender equity and fee-free basic education in Tanzania - Al-Samarrai, Samer; Tamagnan, Marie Evane (Education Global Practice, Africa Region, World Ban, 2019)
Samer Al-Samarrai, Marie Evane Tamagnan1 Introduced in 2016, the Fee-Free Basic Education Program (FBEP) is the government’s flagship policy to expand equitable access to basic education. Evidence shows that policies of this kind increase educational access and lead to significant economic and social benefits. In Ghana, children that received fee-free education were much more likely to complete secondary school and had much higher earnings than children that were not part of the program. In Tanzania, similar benefits to FBEP are possible since the labor market returns to secondary schooling are high.

Interactive apps prevent gender discrepancies in early-grade mathematics in a low-income country in sub-Saharan Africa - Pitchford, Nicola J.; Chigeda, Antonie; Hubber, Paula J. (Developmental Science, 2019)
Globally, gender differences are reported in the early acquisition of reading and mathematics as girls tend to outperform boys in reading, whereas boys tend to outperform girls in mathematics. This can have long-term impact resulting in an under-representation of girls in Science, Technology, Engineering and Mathematics subjects. Recent research suggests that sociocultural factors account for differences across genders in the acquisition of these foundational skills. In this study, we investigated whether a new technology-based intervention, that included activities accessible to both boys and girls, can reduce gender differences from emerging during the early primary school years. The novel instructional method used in this study employed apps developed by onebillion© delivered individually through touch-screen tablets. Over a series of experiments conducted in Malawi, a low-income country in sub-Sahara Africa, we found that when children were exposed to standard pedagogical practice typical gender differences emerged over the first grade (Experiment 1). In contrast, boys and girls learnt equally well with the new interactive apps designed to support the learning of mathematics (Experiment 2) and reading (Experiment 3). When implemented at the start of primary education, before significant gender discrepancies become established, this novel technology-based intervention can prevent significant gender effects for mathematics. These results demonstrate that different instructional practices influence the emergence of gender disparities in early mathematics. Digital interventions can mitigate gender differences in countries where standard pedagogical instruction typically hinders girls from acquiring early mathematical skills at the same rate as boys. A video abstract of this article can be viewed at https://www.youtube.com/watch?v=55x-6hhAY9M&feature=youtu.be
Keywords: education; gender inequity; mathematics; reading; tablet technology

Developing TPACK in science and mathematics teacher education in Tanzania: A proof of concept study - Kafyulilo, Ayoub; Fisser, Petra (Collaborative Curriculum Design for Sustainable Innovation and Teacher Learning, 2019)
Since 1997, the government of Tanzania has made several attempts at introducing technology into education. However, despite these efforts technology has not become integrated into educational practice. A main reason is that teachers do not embrace the use of technology in their teaching. This study was initiated to design, implement and evaluate a professional development arrangement aimed at promoting teachers’ use of technology in their teaching practice. The study started with a ‘proof of concept’ study. Based on experiences in Ghana and Kuwait, a professional development arrangement was developed that incorporated ‘learning technology by design’ to prepare pre-service science and math teachers for using technology in their teaching. The experiences from this study informed the design of a professional development arrangement for practicing science teachers. The iterative design, implementation and evaluation of the professional development arrangements will be presented and discussed.

The Politics of Education in Developing Countries: From Schooling to Learning - Hickey, Sam; Hossain, Naomi (Oxford University Press, 2019)
Why have many developing countries that have succeeded in expanding access to education made such limited progress on improving learning outcomes? There is a growing recognition that the learning crisis constitutes a significant dimension of global inequality and also that educational outcomes in developing countries are shaped by political as well as socio-economic and other factors. The Politics of Education in Developing Countries focuses on how politics shapes the capacity and commitment of elites to tackle the learning crisis in six developing countries: Bangladesh, Cambodia, Ghana, Rwanda, South Africa, and Uganda.The problem of education quality is serious across the Global South. The Politics of Education in Developing Countries: From Schooling to Learning deploys a new conceptual framework-the domains of power approach-to show how the type of political settlement shapes the level of elite commitment and state capacity to improving learning outcomes. The domain of education is prone to being highly politicized, as it offers an important source of both rents and legitimacy to political elites, and can be central to paradigmatic elite ideas around nation-building and modernity. Of particular importance is the relative strength of coalitions pushing for access as against those focused on issues of higher quality education. This book concludes with a discussion of entry points and strategies for thinking and working politically in relation to education quality reforms and critical commentaries.

Country list with HDI, iHDI, MPI and Gini (version 1) - Haßler, Björn; Adam, Taskeen; Brugha, Meaghan; Damani, Kalifa; Allier-Gagneur, Zoe; Hennessy, Sara; Hollow, David; Jordan, Katy; Martin, Kevin; Murphy, Mary; Walker, Hannah (EdTech Hub, 2019)
This is pdf of a country list with HDI, iHDI, MPI and Gini. This file is now superseeded by DOI: 10.5281/zenodo.3908363, see https://docs.edtechhub.org/lib/55A44ZRB (which will also be available as a data file).
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _yl:q; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Keyword inventory (version 1) - Haßler, Björn; Adam, Taskeen; Brugha, Meaghan; Damani, Kalifa; Allier-Gagneur, Zoe; Hennessy, Sara; Hollow, David; Jordan, Katy; Martin, Kevin; Murphy, Mary; Walker, Hannah (EdTech Hub, 2019)
The document contains the keyword inventory used for automated searching. This file is now superseeded by DOI: 10.5281/zenodo.3908363, see https://docs.edtechhub.org/lib/55A44ZRB.
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _yl:p; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode